Golay Coded Sequences in Synthetic Aperture Imaging Systems - Ihor TROTS; Yuriy TASINKEVYCH; Andrzej NOWICKI; Marcin LEWANDOWSKI (Archives of Acoustics)
The paper presents the theoretical and experimental study of synthetic trans- mit aperture (STA) method combined with Golay coded transmission for medical ultrasound imaging applications. The transmission of long waveforms characterized by a particular autocorrelation function allows to increase the total energy of the transmitted signal without increasing the peak pressure. It can also improve signal- to-noise ratio and increase the visualization depth maintaining the ultrasound image resolution. In the work the 128-element linear transducer array with 0.3 mm pitch excited by the 8 and 16-bits Golay coded sequences as well as a one cycle at nominal frequencies 4 MHz were used. The comparison of 2D ultrasound images of the tissue mimicking phantoms is presented to demonstrate the benefits of coded transmission. The image reconstruction was performed using synthetic STA algorithm with transmit and receive signals correction based on a single element directivity function.